ANALISIS EFEKTIFITAS DAN EFISIENSI PAJAK REKLAME, PAJAK PARKIR, PAJAK HIBURAN, PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DAN PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN BANTUL - Teguh Erawati; Nyemas Rahmawati (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2016)
This study aims to determine the growth and role of Advertisement Tax, Tax Parkir and Entertainment Tax on Gross Regional Domestic Product (PDRB) and Revenue First Regional (PAD) in Bantul. To determine the effectiveness and efficiency of the advertisement tax, Parking Tax, Entertainment Tax and Revenue First Regional (PAD) in Bantul. The variables of this research is the advertisement tax, Parkir Tax, Entertainment Tax Gross Regional Domestic Product (PDRB) and revenue First Regional (PAD). The research data is the data type sekuder years 2009 - 2014 was obtained from the study of literature, Dipenda Bantul and the Central Bureau of Statistics of Bantul.Teknik analysis is the analysis of the contribution, effectiveness, and efficiency. The results showed growth billboard tax ranging between 7.79% - 54.91%, or an average annual 18.09% advertisement tax contribution to the PDRB annually on average by 0,016%. While the contribution of the advertisement tax to PAD which is an average of 1.528%. Parkir tax growth ranged between 6.37% - 130.91% or an average annual 48.30% Parkir tax contribution to the GDP average of 0.00037%. While the contribution of tax revenue parking against average of 0.031%. The growth of the entertainment tax ranging between 7.78% - 98.24% Average 47.83% in terms of entertainment tax contribution to the PDRB average of 0.000217%. While the contribution of entertainment tax to PAD is the average per year amounted to 0.183% of the total revenue. Effectiveness analysis realization advertisement tax, tax and entertainment tax parking otherwise very effective, because the results of the calculation of the average in the past 6 years more than 100%. The results of the analysis of the efficiency of the advertisement tax, tax parking and entertainment taxes very own efficient, because the result of calculation of 10%, so it is very efficient because of below 60%, in terms of the cost of harvesting minimal can produce revenues advertisement tax, tax parking and entertainment tax maximum. Keywords: Advertisement tax, Parking Tax, Entertainment Tax, Gross Regional Domestic Product (PDRB) and Revenue First Regional (PAD)